Influence of protostellar outflows on star and protoplanetary disk formation in a massive star-forming clump - Lebreuilly, Ugo; Hennebelle, P.; Maury, A.; González, M.; Traficante, A.; Klessen, Ralf S.; Testi, L.; Molinari, S. (Astronomy and astrophysics, 2024)
Context. Due to the presence of magnetic fields, protostellar jets or outflows are a natural consequence of accretion onto protostars. They are expected to play an important role in star and protoplanetary disk formation. Aims. We aim to determine the influence of outflows on star and protoplanetary disk formation in star-forming clumps. Methods. Using RAMSES, we performed the first magnetohydrodynamics calculation of massive star-forming clumps with ambipolar diffusion; radiative transfer, including the radiative feedback of protostars; and protostellar outflows while systematically resolving the disk scales. We compared this simulation to a model without outflows. Results. We found that protostellar outflows have a significant impact on both star and disk formation. They provide a significant amount of additional kinetic energy to the clump, with typical velocities of around a few 10 km s−1; impact the clump and disk temperatures; reduce the accretion rate onto the protostars; and enhance fragmentation in the filaments. We found that they promote a more numerous stellar population. They do not impact the low-mass end of the IMF much, which is probably controlled by the mass of the first Larson core; however, they have an influence on its peak and high-mass end. Conclusions. Protostellar outflows appear to have a significant influence on both star and disk formation and should therefore be included in realistic simulations of star-forming environments.